Analysis of Precipitable Water Vapour in Angola Using GNSS Observations - Gomes, Isildo Ntemo (2022)
For accurate weather predictions and analysis of extreme events, a good estimate of the amount of water content in the atmosphere is essential. This information is provided by several techniques like radiosondes that measure this parameter at various heights. However, most of them are very limited spatially and temporarily or suffer from measurement specific constraints. To complement these techniques, Precipitable Water Vapor (PWV) can be measured with GNSS (Global Navigation Satellite System) at CORS (Continuously Operating Reference Stations) networks. when the temperature and pressure are also known at the station location. PWV can be derived from the delay in the GNSS signal when it passes through the troposphere. In the framework of SUGGEST-AFRICA, it is being implemented a system to use the national GNSS stations for the automatic computation of PWV in Angola. Thus, this dissertation intends to describe the necessary steps to develop a system to be used for supporting meteorological and climate applications in Angola. SUGGEST-AFRICA also funded the installation of 5 weather stations, collocated with GNSS stations in Angola namely: Benguela, Cabinda, Cuito, Luanda and Namibe, in order to obtain pressure and temperature which is necessary to obtain the PWV estimates. When there are no nearby meteorological stations, the potential alternative is to use values from global/regional models. Methodologies have been optimized to passive and actively access the GNSS data; the PWV estimations are computed using PPP (Precise Point Positioning), which permits the estimation of each station separately; solutions have been validated using internal values. In addition, analyses are presented to evaluate the reliability of the network. This work presents preliminary results for the variation of the ZTD data available all around the territory in Angola and how they relate to the seasonal variations in water vapour. Also, presents preliminary results for the time-series variation of PWV in the Luanda station (collocated by the SEGAL group). This study is supported by SUGGEST-AFRICA, funded by Fundação Aga Khan and FCT. It uses computational resources provided by C4G – Collaboratory for Geosciences (PINFRA/22151/2016). It is also supported by project FCT/UIDB/50019/2020 – IDL funded by FCT.